Maternal mental illness, autonomic nervous system regulation, and romantic relationship outcomes in emerging adults: The TRAILS study - Marija Janković; Stefan Bogaerts; Jelle Sijtsema (Acta Psychologica)
In this study, we investigated the associations of exposure to maternal mental illness with participants' romantic relationship status in youth from a longitudinal population-based study (N = 520, Mage, = 19.0, 51.5 % females), and more qualitative aspects of romantic relationships in those currently in a relationship (n = 252, 54.5 % females). We tested the extent to which these associations were mediated by pre-ejection period (PEP) and respiratory sinus arrhythmia (RSA) reactivity to social stress. In a subsample of individuals currently in a relationship, youth reported on relationship commitment, satisfaction, quality of alternatives, and investment size. Additionally, physical activity was considered a potential moderator of the effects of RSA and PEP reactivity on romantic relationship status. Maternal mental illness did not predict individuals' romantic relationship status. Single participants showed greater reductions in RSA activity during social stress, whereas longer PEP in those romantically involved contributed to more relationship commitment. Physical activity did not significantly moderate any of the investigated relationships. Finally, we established strong measurement invariance of commitment, satisfaction, quality of alternatives, and investment size subscales across genders. This study enhanced our understanding of the role of ANS activity in romantic relationships by demonstrating that lower SNS reactivity and lower PNS withdrawal during social stress led to more favorable relationship outcomes.